Menggunakan Model Penerimaan Teknologi (TAM) untuk Menjelaskan Adopsi Teknologi Digital oleh Guru dalam Bisnis Pendidikan - Nur Rahmi Akbarini (Universitas Pendidikan Ganesha, 2024)
The use of technology eases and makes teaching learning process effective and efficient. Thus far, researches on technology acceptance in higher education has been widely conducted; however, only few has focused on vocational high school teachers, especially in the field of business. This survey research aims to analyze the influences of technology acceptance variables: Perceived of usefulness (PU) and Perceived of Ease of Use (PEU) towards two other acceptance variables: among vocational high school (SMK) teachers in the Business and Management field in Surakarta. The population of this research was all vocational high school teachers in the Business and Management field in Surakarta. At the end of the research, there were 172 responses obtained from the teachers involved. Partial Least Squares (PLS) on Structural Equation Modelling (SEM) was used to test the research hypotheses. The empirical findings show that there are significant influences; particularly on PEU and PU, as well as PEU and PU on BI. Furthermore, BI is also proven to have a significant influence on AU. The findings are expected to provide deeper insights into the factors influencing technology adoption by teachers in business education. Moreover, the implication is foreseen to contribute on the development of more effective and efficient business education through the use of digital technology.